ELECTRICITY PRODUCTION FROM FOOD WASTE LEACHATE USING DOUBLE CHAMBER MICROBIAL FUEL CELL - Willie Prasidha; Akmal Irfan Majid (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2020)
This study was aimed at evaluating the performance of non-aerated and aerated double chamber microbial fuel cells from food waste leachate. The value of open circuit voltage (OCV) and close circuit voltage (CCV) were taken to analyze power density and current density of both configurations. Two double chamber microbial fuel cells (MFC) with different configurations were developed to produce electricity from food waste leachate and studied for 30 days. Anode and catode were made by uncoated carbon felt and graphite rod. Food waste and water were incubated inside a reactor. After 30 days, the electricity production characteristics between the two configurations were obtained. Both configurations reached the same maximum power density and maximum current density but the aerated MFC showed higher performance of maximum open-circuit voltage (OCV), average power density, and current density than non-aerated MFC. The results show that the supplying continuous dissolved air in the cathode chamber resulted in higher voltage, higher average power density, and higher average current density in double chamber microbial fuel cell.